Gambaran Dokter yang Dihadirkan sebagai Ahli dalam Persidangan di Pengadilan Negeri Medan dan Pengadilan Negeri Lubuk Pakam Periode Tahun 2018-2019 - Hasudungan, Boy Oktafianus; Harianja, Dessy Darmayani; Tjiok, Sufida (Universitas HKBP Nommensen, 2023)
Background: The evidence of an occurrence is increasingly developing with the presence of silent witnesses, this type of witness required an expert to be able to explain the occurrence, one of which is a doctor. A doctor must meet the characteristic criteria in order for a doctor to explain a case. Objective : This study aimed to describe characteristics of doctors who are called as experts in the Medan District Court (DC) and Lubuk Pakam DC. Methods : This research was a descriptive qualitative study using a cross-sectional. The number of samples is 145 doctors who were selected using the total sampling method. Primary data from interviews with related doctor, and secondary data in the form of case data presenting them as experts. Result : The results of this study showed 145 doctors, (58,1%) abuse cases in Medan DC, (38,1%) sexual abuse cases in Lubuk Pakam DC, (37,7%) male doctors in Medan DC and (33,3%) Lubuk Pakam DC, (37,7%) the age group 25-34 years in Medan DC and (33,3%) 35-44 year in Lubuk Pakam DC, (25,0%) the duration of doctors was 6-10 year in Medan DC and (23,8%) 31-35 year in Lubuk Pakam DC, Bhayangkara TK II Hospital in Medan DC and Lubuk Pakam DC, general practitioner (57,3%) in Medan DC and doctors forensic (38,1%) in Lubuk Pakam DC, 1 doctors who compensated (0,7%). Conclusion : There were still many doctors who haven’t received reimbursement when presented as experts at the trial. Key Words : Doctor, Expert, Reimbursement.